Classification of Cortical Brain Malformations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Clinical, radiological, and genetic classifications of 113 cases of malformations of cortical development (MCD) were evaluated at the Erasmus Medical Center-Sophia Children's Hospital, Rotterdam, the Netherlands.